Water and moisture permeability of high-temperature vulcanized silicone rubber - Wang, Z.; Zhao, L. H.; Jia, Z. D.; Guan, Z. C. (IEEE transactions on dielectrics and electrical insulation, 2017)
This study focuses on water and moisture permeability of high-temperature vulcanized silicone rubber (HTV SIR) and permeation time of water molecules through SIR sheath. The theoretical expression of permeation time was deduced based on Langmuir diffusion model and the dependence of permeation time on sheath thickness and diffusion parameters of water molecules in sheath was numerically calculated. Results indicate that permeation time increases quadratically with sheath thickness. The influences of some parameters, such as, inorganic filler (fumed silica and aluminum hydroxide) characteristics, sample thickness, AC electric field, and aqueous solution concentration on water permeability of SIR, and the effects of filler characteristics, sample thickness, AC electric field, and relative humidity on moisture permeability of SIR were investigated. Results indicate that hydrophobic treatment of inorganic filler particle surface, moderate increase in filler content and increase in sample thickness can to a certain degree weaken the water and moisture permeability of HTV SIR.